Pendidikan Agama Islam dalam Rehabilitasi Moral Anak Korban Kekerasan - Anita.S; Amaluddin Amaluddin (FKIP UNSULTRA, 2025)
Children who are victims of violence often experience serious psychological, social, and moral impacts. Moral rehabilitation is an important aspect in the recovery process so that children can grow and develop optimally. Islamic Religious Education (PAI) has great potential in providing constructive spiritual and moral solutions for children who are victims of violence. This literature study aims to examine the role of PAI in the process of moral rehabilitation of children who are victims of violence based on the results of previous research, scientific books, and accredited journal articles. The method used is a literature review with a qualitative descriptive approach. The results of the study show that PAI plays an important role in five main aspects: (1) internalization of noble moral values; (2) strengthening children's self-identity through the teachings of monotheism; (3) emotional healing through a worship approach; (4) restoring children's self-confidence through Islamic character building; and (5) social support from the religious environment. PAI is not only an educational instrument, but also a medium for spiritual therapy that can help children recover from the trauma of violence. Integration between religious education, child psychology, and social approaches is needed to create a comprehensive rehabilitation program. This study recommends the need for collaboration between educational institutions, religious educators, psychologists, and child protection institutions in implementing PAI contextually and comprehensively.